• 2022-06-19
    a(a+b)(a-b)-a(a-b)^2,提公因式
  • a(a+b)(a-b)-a(a-b)^2=a(a+b)(a-b)-a(a-b)(a-b)=a(a-b)[(a+b)-(a-b)]=a(a-b)(a+b-a+b)=ab^2(a-b)

    内容

    • 0

      设a,b为实数,且ab<0,则 A: |a+b|>|a-b| B: |a+b|<|a-b| C: |a-b|<||a|-|b|| D: |a-b|<|a|+|b|

    • 1

      设a,b∈R,且ab<0,那么必有(). A: |a+b|>|a-b| B: |a+b|<|a-b| C: |a-b|<||a|-|b|| D: |a-b|<|a|+|b

    • 2

      设A,B是n阶方阵,下列等式成立的是(). A: (A+B)=A+2AB+B B: (A-B)×(A+B)=A-B C: (A+B)×(A-B)=A-B D: (A+B)=A+AB+BA+B

    • 3

      (a+b)2 -( )=(a-b)2

    • 4

      因式分(1)x4-y4(2)x3y-2x2y2+xy3(3)4x2-4x+1(4)4(a-b)2+1+4(a-b)